MORFOLOGIA E MORFOMETRIA DAS DILATAÇÕES GLANDULARES NO ENDOMÉTRIO DA ÉGUA - Monteiro, Cristina Maria Rodrigues [UNESP]; Silva, Carlos Antônio Mondino; Barros, Severo Sales De (Universidade Federal de Santa Maria, 1994)
SUMMARY Endometria of 923 mares were histological reviewed for changes of glandular dilatation. The material originated from 873 uterine biopsies and 50 uterine samples of abattoir. This change was detected in 164 (18,8%) ofthe biopsy cases and in 23 (46%) of the abbatoir cases. From these 30 biopsies and 17 abattoir samples were morphological and morphometrical analysed. Dilatation of endometrial glands were associated with periglandular fibrosis in 68,8% of the biopsy cases and in 86,1% of the abattoir cases. It was not possible to stabilish the cause(s) of glandular dilatation but morphological data suggest a local disturb in the hormonal - stroma cells -extracellular matrix relationship.

RESUMO Os endométrios de 923 éguas foram revisados histologicamente para se verificar a presença de dilatações glandulares. O material se originou de 873 biópsias uterinas e 50 amostras uterinas de matadouro. Esta alteração foi detectada em 164 (18,8%) biópsias e em 23 (46%) casos de matadouro. Destas, 30 amostras de biópsia e 17 de matadouro foram analisadas morfológica e morfometricamente. A dilatação das glândulas endometriais estava associada à fibrose peri-glandular em 68,8% dos casos de biópsia e em 86,1% dos de matadouro. Não foi possível estabelecer a(s) causa(s) da dilatação glandular, mas os dados morfológicos sugerem um distúrbio local na relação entre os hormônios, as células do estrema, as células glandulares e a matriz extracelular.
MORPHOLOGY AND MORPHOMETRY OF THE GLANDULAR DILATATIONS IN THE ENDOMETRIUM OF THE MARE
Keywords: endométrio equino; dilatação glandular; biópsia endometrial; equine endometrium; glandular dilatation; endometrial biopsy